Características geológicas que condicionan los movimientos en masa en el barrio La Banda Alto - Torres Leiva, Fausto Bladimir (2023)
The research work refers to mass movements, which are the displacement of large volumes of material, and their impact on the La Banda Alto neighborhood, located in the city of Loja, Ecuador. The sector has suffered intense landslides that have affected residents and their homes, and has been identified as an area with high and very high threat of mass movements due to geological, topographic, and climatic factors. The importance of studying the geological characteristics of the area is highlighted in order to understand the risk scenario and provide information for mitigation projects. In addition, the uncertainty of knowing the current geological conditions of the neighborhood is mentioned, since it has been some time since the last study was conducted in the area. The La Banda Alto neighborhood has a relief with a slope of 81 meters, with strong slopes and scattered undulations due to the presence of landslides. The study area comprises Quaternary deposits and Middle Miocene rocks belonging to the Trigal Formation, composed of argillites, conglomerates, coarse-grained sandstones, siltstones, and colluvium with clasts of different sizes. Direct shear tests allowed determining the mechanical conditions of the soil, and the saturation map was used to evaluate the soil moisture behavior. A susceptibility map was also developed, identifying the presence of landslides in areas of high susceptibility. However, the lack of reliable precipitation data poses a challenge for determining the exact soil saturation in different areas of the study zone. Keywords: Susceptibility, Mass movements, Saturation, Geology.